Pesantren Bina Umat pada Masa New Normal - Sinta Isthofa Haniek (Al-Riwayah : Jurnal Kependidikan, 2020)
This research aim to know new normal at Islamic Boarding School Bina Umat. The research method uses field research and analysis data is used as qualitative description. The result of the study showed that learning during a pandemic covid-19 demands the application of new normal to be able to run learning activities that cannot continue to be carried out online, because learning in Islamic Boarding School requires practical and continuous learning. New normal can be applied with discipline all of the student, teacher and employees of Bina Umat to always adhere to health. Learning is done by keeping a distance between student and teacher, discipline to use mask where everywhere, wash hand diligently. So that learning at Islamic Boarding School Bina Umat can be carried out. All student have lived a normal life with awareness